PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA UD. CATERING "N" DI SITUBONDO - Yanti, Rizqi; Praja, Yudha; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The business world in the current era is getting tighter, especially in the world of marketing competition, which makes business owners must have a superior strategy in facing competition out there. Business actors are required to have high creativity and innovation in order to attract the attention of consumers in using their services or products. The purpose of this study was to analyze and examine the effect of Product Quality, Service Quality and Price on Repurchase Interest through Consumer Satisfaction as an Intervening Variable at UD. Catering "N" in Situbondo. The target respondents of this research are UD consumers. Catering "N" using the simple random sampling method. Data and hypothesis analysis using the Structural Equation Model-Partial Leas Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that product quality has a significant positive effect on customer satisfaction. Service quality has a positive but insignificant effect on customer satisfaction. Price has a significant positive effect on customer satisfaction. Product quality has a significant positive effect on repurchase interest. Service quality has a significant positive effect on repurchase interest. Price has a significant positive effect on repurchase interest. Customer satisfaction has a significant positive effect on repurchase interest. Product quality has a significant positive effect on repurchase intention through customer satisfaction. Service quality has a positive but insignificant effect on repurchase intention through customer satisfaction. Price has a significant positive effect on repurchase interest through customer satisfaction.